Association between treatment package time and clinical predictors in oropharyngeal cancer. Issue 39 (25th September 2020) - Suzuki, Hidenori; Tamaki, Tsuneo; Tsuzuki, Hidenori; Nishio, Masami; Nishikawa, Daisuke; Beppu, Shintaro; Hanai, Nobuhiro
Abstract : Abstract: The aim of the present study is to investigate the association of treatment package time with the survival outcomes and clinical parameters in patients with oropharyngeal squamous cell carcinoma. A total of 49 patients who underwent definitive treatment were enrolled. The treatment package time was calculated in days from the start of any treatment to the completion of all treatments, including postoperative treatment and salvage surgery for residual tumor. On univariate analyzes, treatment package time ≥118 days, sake index ≥60, Brinkman index ≥450, maximum standardized uptake value ≥42.45, and the presence of synchronous cancer were significantly associated with shorter oropharyngeal squamous cell carcinoma-specific survival. Moreover, a treatment package time of ≥118 days was significantly correlated with shorter overall survival and distant metastasis-free survival. On multivariate analyzes, Brinkman index ≥450 was significantly associated with shorter oropharyngeal squamous cell carcinoma-specific and locoregional recurrence-free survival, and the presence of synchronous cancer was significantly associated with shorter overall and distant metastasis-free survival. In conclusion, a relatively long treatment package time was a predictor of low survival outcomes in oropharyngeal squamous cell carcinoma by univariate analysis.